Attitudes towards immigration: does economic self-interest matter? - Nikolaj Malchow-Møller; Jakob Roland Munch; Sanne Schroll; Jan Rose Skaksen (Institute for the Study of Labor (IZA), 2006)
In this paper, we re-examine the role of economic self-interest in shaping people's attitudes towards immigration, using data from the European Social Survey 2002/2003. Compared to the existing literature, there are two main contributions of the present paper. First, we develop a more powerful test of the hypothesis that a positive relationship between education and attitudes towards immigration reflects economic self-interest in the labour market. Second, we develop an alternative and more direct test of whether economic self-interest matters for people's attitudes towards immigration. We find that while the original relationship between education and attitudes found in the literature is unlikely to reflect economic self-interest, there is considerable evidence of economic self-interest when using the more direct test.
Keywords: 330; Meinung; Einwanderung; Eigeninteresse; EU-Staaten